Análise e Criação de Páginas Web na Vodafone - Guedes, Helena Sofia Soares (2020)
The new online world, that increasingly changes the way people interact with a company, institution or even with other people, demands sets of rules to ensure that the costumer or user has the best experience possible and that this connection is done without compromising the image of the company, brand or institution. In this report I will describe the tasks that I have done during my internship at Vodafone Portugal and that involve the creation of web pages in a telecommunications website. Then correlating with the interaction mention above and so needing a special attention from the user experience perspective.